Profile of Clients Seeking Abortion Care Facilities at a Tertiary Care Center in a Remote Place - Shah, Rajiv; Basnyat, Subi; Panta, Prem Prasad; Thapa, Jwala (Journal of Karnali Academy of Health Sciences, 2020)
Background: It has been shown that the demographic profile, parity, religion, caste and ethnicity plays an important role in the timing of the females seeking abortion care and their choice of contraception. So, we wanted to conduct this study to access the demographic profile of the abortion seekers in the study area and the relation of these to the timing of seeking safe abortion services and to their choice of contraceptives. Methods: This was a descriptive cross-sectional study conducted at KAHS, Jumla. The sampling technique was census sampling. The data analysis was done with the help of SPSS version 16 software. For descriptive statistics frequency and percentages, and for the inferential statistics Chi-square test was used. P value less than 0.05 was used for statistical significance. Results: There were total of 163 clients who had received comprehensive abortion care during the study period. About 63.8% females were Brahmin and Chetri and 20.9% were dalits. Most of the females were in the age group of 18-20 and 21-35 years (36.2 % and 36.8%). Also most of the females had either no schooling (25.8%) or only primary level of schooling (38.7%). 24.5% of the females were unmarried in our study. Younger age group and unmarried status was significantly associated with late presentation. There was less acceptance of LARCs in the unmarried females (27.5%), females from rural populations (38.6%), primigravidas (13.7%) and among non-dalits (38.0%). Conclusion: Timing of abortion is correlated to the demographic profile with the younger females, lower literacy status, females from the rural area, unmarried, under-privileged and primigravida tend to present later in the pregnancy for abortion. This also play a significant role in their choice of more reliable contraception. So, we should focus the awareness program in these females.